Enhanced Photocatalytic Activity and Selectivity for CO2 Reduction over a TiO2 Nanofibre Mat Using Ag and MgO as Bi‐Cocatalyst. Issue 1 (5th October 2018) - Xu, Feiyan; Meng, Kai; Cheng, Bei; Yu, Jiaguo; Ho, Wingkei
Abstract: The design and preparation of novel photocatalysts to enhance photocatalytic activity and selectivity for CO2 reduction is highly important both theoretically and practically. Herein, we develop an electrospinning and wet‐impregnation method to obtain an Ag and MgO co‐modified TiO2 nanofibrous mat. Ag nanoparticles (NPs) as electron traps can effectively separate electron−hole pairs and reduce their recombination in TiO2 nanofibres due to the formation of Schottky barriers. Accumulation of photogenerated electrons in the Ag NPs can enhance the formation of CH4 . The obtained Ag−MgO−TiO2 composite mat exhibits extended visible light absorption owing to the surface plasmon resonance effect of the Ag NPs. Deposition of MgO NPs, as basic sites, could facilitate the adsorption of CO2 molecules. The synergetic effects of Ag and MgO as a bi‐cocatalyst contribute to enhanced photocatalytic activity and CH4 ‐selectivity for CO2 reduction. Isotope ( 13 C) tracer experiments confirm that the products are produced from photocatalytic reduction of the CO2 source instead of organic contaminants. This report highlights the importance of the synergistic effect of Ag and MgO NPs on enhancing the photocatalytic activity and selectivity of TiO2 ‐based materials. Abstract : Putting the mat in material : A Ag−MgO−TiO2 nanofibrous mat shows improved photocatalytic activity and selectivity for CO2 reduction on account of enhanced CO2 adsorption, reduced photogenerated charge carrier recombination and electron accumulation on Ag NPs.